2021
DOI: 10.1002/chem.202005392
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Zinc Hydride Catalyzed Carbon Dioxide Reduction to Formate: Deciphering Elementary Reactions, Isolation of Intermediates, and Computational Investigations

Abstract: Zinc has been an element of choice for carbon dioxide reduction in recent years. Zinc compounds have been showcased as catalysts for carbon dioxide hydrosilylation and hydroboration. The extent of carbon dioxide reduction can depend on various factors, including electrophilicity at the zinc center and the denticity of the ancillary ligands. In a few cases, the addition of Lewis acids to zinc hydride catalysts markedly influences carbon dioxide reduction. These factors have been investigated by exploring elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 64 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…20 Specifically, CO 2 inserts into the Zn–H bond of [Tptm]ZnH to form the zinc formate species, [Tptm]ZnO 2 CH, 21,22 which subsequently undergoes metathesis with (RO) 3 SiH to release HCO 2 Si(OR) 3 and regenerate [Tptm]ZnH, a mechanism which is analogous to that proposed for other hydrosilylation reactions. 17,23 The catalytic synthesis of silyl formates is of interest because such compounds have a variety of applications, including uses in organic syntheses. 24,25 The zinc-catalyzed synthesis of HCO 2 Si(OEt) 3 may also be conducted without the need of additional solvent; in this regard, the solvent-free conversion of CO 2 to silyl formates has been recognized as an important advance 26 according to the principles of Green Chemistry, 27,28 since it minimizes the use of unnecessary solvent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Specifically, CO 2 inserts into the Zn–H bond of [Tptm]ZnH to form the zinc formate species, [Tptm]ZnO 2 CH, 21,22 which subsequently undergoes metathesis with (RO) 3 SiH to release HCO 2 Si(OR) 3 and regenerate [Tptm]ZnH, a mechanism which is analogous to that proposed for other hydrosilylation reactions. 17,23 The catalytic synthesis of silyl formates is of interest because such compounds have a variety of applications, including uses in organic syntheses. 24,25 The zinc-catalyzed synthesis of HCO 2 Si(OEt) 3 may also be conducted without the need of additional solvent; in this regard, the solvent-free conversion of CO 2 to silyl formates has been recognized as an important advance 26 according to the principles of Green Chemistry, 27,28 since it minimizes the use of unnecessary solvent.…”
Section: Resultsmentioning
confidence: 99%
“…8,11 However, since many of these catalysts employ precious metals, there is interest in discovering catalysts that employ nonprecious metals, such as zinc. 8,16–18 Therefore, we describe here the use of a zinc hydride compound, namely [tris(2-pyridylthio)methyl]zinc hydride, [Tptm]ZnH (Fig. 1), 19 to serve as a catalyst for the hydrosilylation of CO 2 to the methanol level.…”
Section: Introductionmentioning
confidence: 99%
“…We have modified this procedure by using Lewis base adducts of molecular AlH 3 . These well-known compounds including commercially available [AlH 3 (NMe 2 n Bu)] have found applications as precursors for reduction and hydroalumination reagents or aluminum nanoparticles. , The stability of [AlH 3 (NR 3 )] depends on the steric demand of the amine donor and follows the order NMe 3 < NMe 2 Et < NMe 2 n Bu < NEt 3 . The reaction of LiAlH 4 with [NEt 3 H]Cl in n -pentane quantitatively gave the alane adduct [AlH 3 (NEt 3 )] with concomitant evolution of dihydrogen gas (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…As was previously reported, a pseudotricoordinate zinc hydride cation of the type [(L 2 )­ZnH] + can be assumed to be the catalytically active species. However, a higher coordination number does not lower the activity by virtue of zinc’s ability to “hypervalency”, that is, to expand the coordination number >4 . Literature reports on tricoordinate zinc hydride catalysts supported by bulky nacnac and related ligands of LX-type as well as hemilabile derivatives of L 2 X-type show also high activity, albeit depending on the steric environment of the zinc center.…”
Section: Discussionmentioning
confidence: 99%
“…based catalysts are highly desirable. [11][12][13][14] For example, Gerard Parkin et al reported that {[κ 3 -Tptm]M}[HB(C 6 F 5 ) 3 ] catalytic systems could efficiently catalyze a CO 2 hydrosilylation reaction, in which a magnesium-based complex showed efficient capability for the CO 2 reduction reaction. 15 Catalytic hydroboration of CO 2 is an alternative method for efficiently transforming CO 2 to valuable compounds.…”
Section: Introductionmentioning
confidence: 99%